Has a Prescription-limiting Law in Rhode Island Helped to Reduce Opioid Use After Total Joint Arthroplasty?. Issue 2 (February 2020) - Reid, Daniel B.C.; Shapiro, Benjamin; Shah, Kalpit N.; Ruddell, Jack H.; Cohen, Eric M.; Akelman, Edward; Daniels, Alan H.
Abstract: Background: In the United States, since 2016, at least 28 of 50 state legislatures have passed laws regarding mandatory prescribing limits for opioid medications. One of the earliest state laws (which was passed in Rhode Island in 2016) restricted the maximum morphine milligram equivalents provided in the first postoperative prescription for patients defined as opioid-naïve to 30 morphine milligram equivalents per day, 150 total morphine milligram equivalents, or 20 total doses. While such regulations are increasingly common in the United States, their effects on opioid use after total joint arthroplasty are unclear. Questions/purposes: (1) Are legislative limitations to opioid prescriptions in Rhode Island associated with decreased opioid use in the immediate (first outpatient prescription postoperatively), 30-day, and 90-day periods after THA and TKA? (2) Is this law associated with similar changes in postoperative opioid use among patients who are opioid-naïve and those who are opioid-tolerant preoperatively? Methods: Patients undergoing primary THA or TKA between January 1, 2016 and June 28, 2016 (before the law was passed on June 28, 2016) were retrospectively compared with patients undergoing surgery between June 1, 2017 and December 31, 2017 (after the law's implementation on April 17, 2017). The lapse between the pre-law and post-law periods was designed to avoid confounding from potential voluntary practice changes by physicians after the law was passed but before its mandatory implementation. Demographic and surgical details were extracted from a large multi-specialty orthopaedic group's surgical billing database using Current Procedural Terminology codes 27130 and 27447. Any patients undergoing revision procedures, same-day bilateral arthroplasties, or a second primary THA or TKA in the 3-month followup period were excluded. Secondary data were confirmed by reviewing individual electronic medical records in the associated hospital system which included three major hospital sites. We evaluated 1125 patients. In accordance with the state's department of health guidelines, patients were defined as opioid-tolerant if they had filled any prescription for an opioid medication in the 30-day preoperative period. Data on age, gender, and the proportion of patients who were defined as opioid tolerant preoperatively were collected and found to be no different between the pre-law and post-law groups. The state's prescription drug monitoring program database was used to collect data on prescriptions for all controlled substances filled between 30 days preoperatively and 90 days postoperatively. The primary outcomes were the mean morphine milligram equivalents of the initial outpatient postoperative opioid prescription after discharge and the mean cumulative morphine milligram equivalents at the 30- and 90-day postoperative intervals. Secondary analyses included subgroup analyses by procedure and by preoperative opioid tolerance. Results: After the law was implemented, the first opioid prescriptions were smaller for patients who were opioid-naïve (mean 156 ± 106 morphine milligram equivalents after the law's passage versus 451 ± 296 before, mean difference 294 morphine milligram equivalents; p < 0.001) and those who were opioid-tolerant (263 ± 265 morphine milligram equivalents after the law's passage versus 534 ± 427 before, mean difference 271 morphine milligram equivalents; p < 0.001); however, for cumulative prescriptions in the first 30 days postoperatively, this was only true among patients who were previously opioid-naïve (501 ± 416 morphine milligram equivalents after the law's passage versus 796 ± 597 before, mean difference 295 morphine milligram equivalents; p < 0.001). Those who were opioid-tolerant did not have a decrease in the cumulative number of 30-day morphine milligram equivalents (1288 ± 1632 morphine milligram equivalents after the law's passage versus 1398 ± 1274 before, mean difference 110 morphine milligram equivalents; p = 0.066). Conclusions: The prescription-limiting law was associated with a decline in cumulative opioid prescriptions at 30 days postoperatively filled by patients who were opioid-naïve before total joint arthroplasty. This may substantially impact public health, and these policies should be considered an important tool for healthcare providers, communities, and policymakers who wish to combat the current opioid epidemic. However, given the lack of a discernible effect on cumulative opioids filled from 30 to 90 days postoperatively, further investigations are needed to evaluate more effective policies to prevent prolonged opioid use after total joint arthroplasty, particularly in patients who are opioid-tolerant preoperatively. Level of Evidence: Level III, therapeutic study.